Development of a system dynamic model for aggregate planning in supply chain - Sadeghiamirshahidi, Narjes (2014)
Supply chain is a series of different members which are connected to each other in order to satisfy a customer demand. Traditionally each members of supply chain operate independently but in today’s global market coordination of different members of the supply chain is necessary. Recently production planning in aggregate level for different units of supply chain is one of the most important issues. Due to the dynamic nature of planning system within the supply chain, a decision taken in one time influences the decision taken in later time. Therefore a time-based dynamic model which capture the relationships between different parameters of supply chain is required .This study attempts to develop a system dynamic model for supply chain planning of a manufacturing company in aggregate level by considering feedback loop structure. The dynamic model is constructed by Vensim PLE software to represent the production rate, inventory level, and order backlog of two products of the company. The proposed model is also used to investigate different aggregate planning strategies to make decision policies. The generated results are compared in terms of different costs and the best alternative is suggested.